Effect of electrochemical anodization and growth time on continuous growth of carbon nanotubes on carbon fiber surface. Issue 20 (15th October 2022) - Jiang, Haotian; Wang, Yanxiang; Wang, Chengjuan; Xu, Xiaodan; Li, Mengfan; Xu, Zhenhao; Tan, Hongxue; Wang, Yapeng
Abstract: Carbon nanotubes (CNTs)/carbon fiber (CF) reinforcements were prepared by chemical vapor deposition after electrochemical anodization and catalyst impregnation. The results showed that after the electrochemical anodization, the CFs were oxidatively etched and the surface roughness increased, which is helpful to form a uniform catalyst coating on the surface of CF. Under the current of 0.4 A and 0.6 A, CNTs can grow evenly on the surface of CF. Within a certain range, with the increase of growth time, the density and length of CNTs are improved. The CNTs/CF reinforcement prepared at the current intensity of 0.4 A and the growth time of 8 min has the best comprehensive performances compared with other as-fabricated samples. The tensile strength of the sample can reach a high value of 4.56 GPa, and the wettability of resin has an effective improvement.